2016
DOI: 10.1002/dev.21469
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and dyadic associations between expectant parents’ prenatal hormone changes and postpartum parenting outcomes

Abstract: During the transition to parenthood, both men and women experience hormone changes that are thought to promote parental care. Yet very few studies have explicitly tested the hypothesis that prenatal hormone changes are associated with postpartum parenting behavior. In a longitudinal study of 27 first-time expectant couples, we assessed whether prenatal hormone changes predicted self and partner-reported parenting outcomes at three months postpartum. Expectant fathers showed prenatal declines in testosterone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 72 publications
(114 reference statements)
8
51
0
1
Order By: Relevance
“…We also found some modest evidence for associations between lower E2 and fathers' greater participation in daily childcare. Both of these results for paternal psychobiology parallel recent work by Edelstein et al (, ). In their study of U.S. men, they also found that E2 declines significantly across the transition to parenthood.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also found some modest evidence for associations between lower E2 and fathers' greater participation in daily childcare. Both of these results for paternal psychobiology parallel recent work by Edelstein et al (, ). In their study of U.S. men, they also found that E2 declines significantly across the transition to parenthood.…”
Section: Discussionsupporting
confidence: 87%
“…A study of Canadian men showed that expectant and new fathers' E2 was higher compared with non‐fathers, preliminarily suggestive of direct upregulation of fathers' E2 in the peripartum period (Berg & Wynne‐Edwards, ). Contrasting with those results, a recent longitudinal study of pregnant women and their male partners found that fathers' E2 decreased across the pre‐partum period and that fathers with larger E2 declines from the early to late pre‐partum were more involved with household duties and care of infants after the birth (Edelstein et al, ; Edelstein et al, ). These findings closely align with prior research showing longitudinal declines in men's T when they transition to fatherhood and marriage in some settings (Edelstein et al, ; Edelstein et al, ; Gettler, McDade, Agustin, Feranil, & Kuzawa, ; Gettler, McDade, Feranil, & Kuzawa, ; Holmboe et al, ; Mazur & Michalek, ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is plausible that women with relatively lower OT and higher T are more effective at responding to challenges from their partners and at establishing greater equity and lower conflict within the dyad. These questions of directionality merit exploration in future longitudinal research, as has been conducted for paternal psychobiology elsewhere (Edelstein et al, ; Gettler, Ryan, et al, ; Saxbe, Edelstein, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research in multiple societies has shown that men and women often have lower T when they have young children that require intensive childcare (Alvarado et al, 2015;Barrett et al, 2013;Gray, Kahlenberg, Barrett, Lipson, & Ellison, 2002;Kuzawa, Gettler, Huang, & McDade, 2010). In some cultural settings, fathers also have reduced T when they engage in more nurturant, direct caregiving (Alvergne, Faurie, & Raymond, 2009;Edelstein et al, 2017;Gettler, McDade, Agustin, Feranil, & Kuzawa, 2015;Kuo et al, 2018;Mascaro, Hackett, & Rilling, 2013;Weisman, Zagoory-Sharon, & Feldman, 2014). U.S. men and women with lower T also report greater commitment and satisfaction in their romantic relationships, as do their partners (Edelstein, van Anders, Chopik, Goldey, & Wardecker, 2014;Saxbe, Edelstein, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%